2022
DOI: 10.3389/fnagi.2022.960479
|View full text |Cite
|
Sign up to set email alerts
|

Pitx3 deficiency promotes age-dependent alterations in striatal medium spiny neurons

Abstract: BackgroundThe classical motor symptoms of Parkinson’s disease (PD) are tightly linked to the gradual loss of dopamine within the striatum. Concomitantly, medium spiny neurons (MSNs) also experience morphological changes, such as reduced dendritic complexity and spine density, which may be potentially associated with motor dysfunction as well. Thus, MSNs may serve as the emerging targets for PD therapy besides the midbrain dopaminergic neurons.ResultsTo comprehensively examine pathological alterations of MSNs l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The PITX3 deficiency can lead to the loss of the substantia nigra striatum path, the deprivation of dopaminergic neurons in the substantia nigra, and the impairment of dopaminergic development, which may drive the development of Parkinson's disease (64). In a TH-Cre/ Pitx3-fl/fl (Pitx3cKO) mouse model, it was noticed that Pitx3 deficiency promotes age-dependent alterations in striatal medium spiny neurons (65). Although many studies have shown the link between PITX3 and Parkinson's disease, the clear association with TS is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The PITX3 deficiency can lead to the loss of the substantia nigra striatum path, the deprivation of dopaminergic neurons in the substantia nigra, and the impairment of dopaminergic development, which may drive the development of Parkinson's disease (64). In a TH-Cre/ Pitx3-fl/fl (Pitx3cKO) mouse model, it was noticed that Pitx3 deficiency promotes age-dependent alterations in striatal medium spiny neurons (65). Although many studies have shown the link between PITX3 and Parkinson's disease, the clear association with TS is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the morphologies of medium spiny neurons (MSNs) were altered due to Pitx3 deficiency, including nuclear, soma, and dendritic atrophy, as well as an increased number of nuclear invaginations. Additionally, more nuclear DNA damages were observed in MSNs during aging, while Pitx3-deficiency aggravated this phenomenon, together with alterations of the DNA methylation profiling associated with lipoprotein and nucleus pathways at late stages [42,93], suggesting that early perturbations of neurotransmitters within MSNs may potentially contribute to the alterations of metabolism, morphology, and epigenetics within the striatum at late stages.…”
Section: Development Of Pitx3-deficient Mouse Modelsmentioning
confidence: 98%
“…Additionally, given that Pitx3 is an essential transcription factor for mDA development, Pitx3-deficient mice represent a useful tool that permits the study of early events in mDA formation. Moreover, studies have reported that Pitx3 −/− mice produce decreased DA signaling rates and induce motor deficits [92] and can be also used to study the morphological and physiological modulation of striatal neurons [93] even after the administration of L-DOPA or other PD-related drugs [94].…”
Section: Development Of Pitx3-deficient Mouse Modelsmentioning
confidence: 99%